An Introduction to Theological Anthropology : Humans, Both Creaturely and Divine - Farris, Joshua R. (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2020)
In this thorough introduction to theological anthropology, Joshua Farris offers an evangelical perspective on the topic. Farris walks the reader through some of the most important issues in traditional approaches to anthropology, such as sexuality, posthumanism, and the image of God. He addresses fundamental questions like, Who am I? and Why do I exist? He also considers the creaturely and divine nature of humans, the body-soul relationship, and the beatific vision
Introduction: Where do we begin? : humans, prolegomena, and method -- What am I? : creaturely and redemptive identity -- What am I and where did I originate? : are we apes, humans, or gods? -- What am I in relation to God? : the image as creaturely and divine -- What does it mean to be free? : freedom as creaturely and divine -- Who am I at birth? " original sin and creaturely failure -- Who am I in Christ? : humans, descended and ascended -- Who are we in culture? : creaturely and divine in work, race, and disability -- Who are we as male and female? : humans as gendered and sexual -- Why am I here? : creaturely living, dying, and the in-between -- Why do I exist? : creaturely process and divine destiny -- Conclusion : Where do we go from here?
Includes bibliographical references and indexes
Keywords: Anthropology; Man - Christian Theology; Anthropology - Biblical Doctrines; Theological anthropology -- Christianity